Sistem informasi nilai akademik mahasiswa menggunakan teknik json dan nfc - Arif Harbani; Ari Fajrianto (Teknois : Jurnal Ilmiah Teknologi Informasi dan Sains, 2019)
Higher education as an institution engaged in the field of science can take advantage of technological developments. One of them is in terms of flexibility and efficiency of students in accessing the data they need related to academic activities in higher education such as student value information. This study aims to make it easy for students to be able to access value information easily. The development model used in this study is a prototype by making an application using NFC and JSON technology as a message format. This research was conducted at STIKOM Binaniaga Bogor with 60 students as samples of application trial subjects. The results of the analysis showed 85.63% of the level of appropriateness of the application, it shows with NFC technology and the application can facilitate students in getting information on student academic values.